Gaya Bahasa Perempuan Dalam Media Baru - Watie, Errika Dwi Setya (Universitas Semarang, 2013)
Media is a means for someone to be able to convey information to others. Currently there are two classes of media. Old media / conventional and new media. Ideally, on the both media, the position and status of all users are the same media. But in reality, in this case, social media as part of the new media, it still occurs mute identity in social media for some women. Based on the observations, a style that used by women on her status in her social media account is still much that is likely to show a distinctive feminine style, which tends to give priority to the relationship, avoid disputes, and minimize the dominant impression